Speciation and release risk of heavy metals bonded on simulated naturally-aged microplastics prepared from artificially broken macroplastics. (15th February 2022) - Chen, Gaobin; Fu, Qianmin; Tan, Xiaofei; Yang, Hailan; Luo, Yang; Shen, Maocai; Gu, Yanling
Abstract: The negative impact of microplastics (MPs) act as metals vectors to environment and ecosystem have been paid more and more attention, and the accumulation risk of them to human body through the food chains and food webs needs to attract attention. In addition, the MPs bonded with heavy metals transport from river into the sea with high salinity may also have metals release risk. Herein, natural aged microplastics prepared from artificially broken macroplastics adsorbed with heavy metals accumulated from the natural environment were tested for their states and release risk in several simulated solution (NaCl and gastrointestinal solutions) to understand their effects on environment and human health. The adsorption capacity of different heavy metals on MPs was different during natural aging process proved by four-acid digestion method. Metals with high accumulation (including Pb, As, Cr, Mn, Ni, Zn, Co, Cu and Cd) on NAMPs were selected for further study. Results obtained via three-step extraction method showed that these heavy metals were mainly present as acid-extractable and reducible ions, which were characterized by high bioavailability. Release experiments suggested the notable Mn, Zn, As, Cr, Cu and Ni release in NaCl solution, and significant release of Mn, Zn, As, Cr, Cu, Pb and Ni in gastrointestinal solutions. The high metal release ratio in the simulated gastric solution was attributed to the weak binding of metal ions to NAMPs in acidic environment. This study will play a vital rule in assessing the ecological risks associated with MPs in natural environment. Graphical abstract: Image 1 Highlights: Microplastics (MPs) accumulated heavy metal ions during the natural aging process. Heavy metals were mainly present as acid-extractable and reducible ions on MPs. Notable metals release in the NaCl and gastrointestinal solutions were observed. The acidic environment was unfavorable for the binding of metal ions to NAMPs. Dissolution of mineral particles bonded with metals was account for metals release.